Caliber of common bile duct.: its diagnostic significance - Delgado, Bolívar; Perrier, José P (Cirugía del Uruguay, 1978)
Its significance for the purpose of diagnosis. In a series of 100 patients the caliber of common bile duct was measured by means of cholangiographic studies with manometric control. The following conclusions were derived: 1) Caliber of normal hile duct increases with age; 2) no evidence was found of "vicarious" dilation of common bile duct in cholecystectomized patients or in those in whom the gall bladder had been excluded, in the absence of choledocus pathology; 3) Pathology probability increases in proportion to, the enlarged caliber of common bile duct; up to 91,6 % in cases when it exceeds 20 mm; 4) However, 19 % of lithiasis was found in common bile ducts of normal caliber; 5) In 12 % of dilated choledocus no present pathology was found. These findings are compared to those of other authors.